THE USE OF JIGSAW COLLABORATIVE LEARNING METHOD IN IMPROVING STUDENT’S READING COMPREHENSION AT MA-ALMUNAUWARAH LOLEOJAYA - Yamin, Desiratnawati; yetty, yetty; Ismail, Ade (FKIP Universitas Khairun, 2023)
The aim of this research is to improve students' reading comprehension using jigsaw collaborative learning method. This research used a pre-experimental research design. The sample consisted of 24 class XI students at Ma-Almunauwarah Loleojaya. Participants in this research were selected using purposive sampling technique. The instrument used in data collection in the pre-test and posttest is multiple choice. The researcher found that the pre-test data was lower than the posttest. It means that the results are included in the positive category. The research results obtained a sig value 2-tailed=0.0010.05. Therefore, Ho was rejected and Ha was accepted. It showed that the learning outcomes of class XI students using jigsaw collaborative learning method are higher than those using conventional method at Ma-Almunauwaraha Loleojaya. So that users of the jigsaw collaborative learning method can improve students’ reading comprehension. The use of the jigsaw in collaborative learning model in English subjects implicated to improve student learning achievement. The students are interested in the learning provided and students do not get bored with learning activities so that student learning outcomes can improve well.